The impostor phenomenon: a look at the outside, the inside, and the other side through scholarly personal narrative - Taylor, Andrea Lyn, author; Timpson, William M., advisor; Dickmann, Ellyn M., advisor; Banning, James H., committee member; Bundy-Fazioli, Kimberly, committee member (Colorado State University. Libraries, 2009)
The purpose of the study was, first, to fully explore the research related to the psychological construct of the Impostor Phenomenon and then to share personal experiences that would help inform and enlighten others as I had been informed and enlightened during the process. In order to accomplish this I researched and documented a comprehensive look at everything published from 1974, the year that Dr. Pauline Rose Clance and Dr. Suzanne Imes coined the term, to the date of this dissertation. Included in this study were all dissertations and peer-reviewed journal articles that directly speak to the topic; excluded were masters' theses. A separate Impostor Reference page is provided (see p. 162). My goal from the beginning was to engage the reader in the research and the narratives that followed so as not to be boring (Jensen, 2004) while I sought to answer my initial research question: Does writing my story from the perspective of an "impostor" help me and my readers to discover and understand the basis for and impact of the Impostor Phenomenon in our lives? Then, like most qualitative inquiries, a secondary question surfaced: How does one move on from a blighted childhood to flourishing adulthood? My hope is that by writing a Scholarly Personal Narrative I have provided evidence that this methodology "can reach, and even surpass, a professional school's highest scholarly standards" as Nash (2004, p. 3) asserts it can, and to provide "validity of an alternative form of intellectual inquiry" (p. 4).
Department Head: Sharon K. Anderson.